ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN PARIWISATA DI BURSA EFEK INDONESIA - Mega Anik Purnama Sari, - (2019)
This research is a quantitative research that aims to determine the effect of Profitability, Asset Structure and Firm Size on Capital Structure. The population in this study are all Tourism sub-sector companies in Indonesia Stock Exchange during the 2015-2017 period. The sampling technique that used is purposive sampling, by that technique the final sample was 11 companies. In this study, the data collection methods is non-behavioral observation. The source of data is a secondary data from Indonesia Stock Exchange website. Data analysis technique that used is descriptive statistics and panel data regression analysis with help of Microsoft Excel 2010 and E-Views version 9.0 programs. Based on the test results that (1) Profitability have negative effect on Capital Structure, (2) Asset Structure does not effect on Capital Structure and (3) Firm Size have positive effect on Capital Structure.